Pencegahan Stunting Melalui Edukasi Pada Masyarakat Kelurahan Pematang Reba - Auradian Marta; Atikah Haura; Delra Maulida Risma; Novriza Awwalin Nisa; Mutiara Rizkia; Nur Fauziah Subati; Putri Ramadhani; Reza Putri Harnefi; Yogi Wirandicha; Vannesah Nara Tasya Halim (ABDI: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
The purpose of this journal is to contribute ideas based on science in the problem of developing the quality of human health, in the sense of informing the public about the dangers of stunting and how to prevent and detect stunting in the Pematang Reba village community. Stunting is a condition where a person's height is shorter/lower than the height of other people in general (of the same age). Stunting is caused by a lack of nutritional intake for a long time, this causes problems in the future, namely experiencing difficulties in achieving optimal physical and cognitive development. Based on the results of community service activities in the context of Stunting Prevention Through Education for the community which is carried out through electronic and non-electronic information media or media, the Kukerta team has carried out various series of outreach activities, namely the distribution of educational videos, distribution of brochures and the creation of stunting banners with the aim of reducing numbers stunting and provide information about stunting to the Pematang Reba Village Community